Enhancing investment in soil health and carbon storage: Hackathon Day One Deep Dives - CGIAR Research Program on Climate Change, Agriculture and Food Security; Nature Conservancy; 4 Per 1000 Initiative; World Bank (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In this session of the two-day hackathon, participants sought to identify different soil carbon accounting approaches and issues that need to be addressed for these approaches to be used by the finance community and develop a collective understanding of available approaches to prepare for the next hacking session.